The development of multimedia interactive courseware package: English phonetics and phonology for undergraduates students / Azidatun-Noor Saidin - Saidin, Azidatun-Noor (2012)
Learning English pronunciation is one of the essential courses for students of English for Second Language (ESL) and English for Foreign Language (EFL). It requires self-learning and practices outside the classroom to enhance students' skills. However, in this great technology world that provides various computer aided language learning, there are educators who still prefer to use traditional ways (or textbook) as a primary method in teaching English. Due this reason, this study aims to develop an alternative for the educators and learners; Multimedia Interactive Learning Courseware for English Phonetics and Phonology; and to evaluate interface design and students' motivation towards this courseware. The development of this prototype requires an instructional model, which is ADDIE model as a step-by-step guidance to complete the development; and usability testing and questionnaire to evaluate the interface design and the motivation of the participants towards the courseware. Using ADDIE model, this prototype is successfully developed. Results from the usability evaluation and questionnaire shows positive feedback regarding interface design of the courseware i.e. text, images, animations and audio. Positive feedback also was found in this study for motivation towards using this courseware. Results also suggest that good interface design invites and motivate participants to use the courseware. Good interface also accommodate learners in the learning process.